The Effect of Dehydration on the Development of Endothelial Dysfunction in Young Athletes: a Comparative Analysis of the Effectiveness of a New Honey Isotonic Drink and Standard Means of Restoring Hydro-Electrolytic Balance - V. N. Kim (Scientific Сentre for Family Health and Human Reproduction Problems, 2020)
Aim of the research. To prove the effectiveness of using isotonic honey drink “Gold F25 IsoDrink Light” (IsoDrink-L) based on the study of the hydration process and endothelial function in young athletes. Materials and methods. A randomized controlled study was performed in young athletes under the age of 18 years. Athletes of the main group (n = 40) consumed IsoDrink-L for a month; athletes of the control group (n = 34) consumed water and isotonic drink “X”. A bioimpedance-based device was used to determine the total amount of water, the absolute and relative proportions of intra- and extracellular water, as well as the ratio of extracellular water to the total amount of water. Hematocrit, specific gravity and color of morning urine, samples with reactive hyperemia and hyperventilation in the brachial artery, including the determination of the endothelial sensitivity index were assessed.Results. All athletes had dehydration in the form of extracellular dehydration, cellular hyperhydration, “blood  thickening”, hyponatremia, increased specific gravity and urine color, as well as endothelial dysfunction. All  symptoms disappeared after using IsoDrink-L for 1 month. No dynamics was observed in the control group,  where 95 % of the athletes took water and 5 % – isotonic drink “X”. ROC analysis showed that the endothelial sensitivity index with a sensitivity of 95.8 % and a specificity of 99.4 % detects endothelial dysfunction. The canonical correlation coefficient between the set of hydration-dependent and endothelium-dependent signs was R = 0.71 (p < 0.0001). We established the danger of uncontrolled water consumption for rehydration in young athletes, as well as the high efficiency of isotonic honey drink and the evidence for its use for the correction of dehydration and endothelial dysfunction. A low awareness of athletes, doctors and coaches about the importance of using effective methods of rehydration in children’s sports was revealed.Conclusion. It was found that water imbalance in young athletes directly or indirectly contributes to the development of endothelial dysfunction, thereby increasing cardiovascular risk. Original approaches to the development of honey isotonic drink for young athletes with proven hydrating and endothelium-protective properties are proposed.